What is Scopus? - Elsevier (Elsevier, 2021)
Scopus is a source-neutral abstract and citation database curated by independent subject matter experts who are recognized leaders in their fields. Scopus puts powerful discovery and analytics tools in the hands of researchers, librarians, research managers and funders to promote ideas, people and institutions.